FRAÇÕES LÁBEIS E RECALCITRANTES DE CARBONO DO SOLO EM DIFERENTES SISTEMAS MANEJADOS AO LONGO DE 12 ANOS - Maiane Mendes da Silva , Ozielly; Sérgio Rosset , Jean; Vieira dos Santos , Wesley; Panachuki , Elói; Maria Cutier Dominguez Pereira , Cecília; Vitor Fabian Salvador , João (ANAIS DO ENIC, 2026)
-